PENGARUH UMUR PINDAH TANAM DAN JENIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERONG (Solanum melongena L.) - Fitriany Primawati; Djarwatiningsih P.S.; Agus Sulistyono (Plumula : Berkala Ilmiah Agroteknologi, 2022)
Eggplant (Solanum melongena L.) is a vegetable that is cultivated for its fruit in terms of nutrition and the price of eggplant is a commodity that is experiencing an increase in demand. This study aims to determine the age of transplanting and the best type of liquid organic fertilizer on the growth and yield of eggplant. This research was conducted in January-April 2021 in the experimental field of the Faculty of Agriculture, National Development University "Veteran" East Java. This study used a completely randomized design (RAL) with two factors, namely the age of transplanting and the type of liquid organic fertilizer with 16 treatment combinations repeated 3 times. The first factor is the age of transplanting with 4 levels, namely the age of seedlings 10 days, 20 days, 30 days, and 40 days. While the second factor is the type of liquid organic fertilizer with 4 levels of NPK fertilizer 20 grams/plant, banana weevil 150 ml/plant, Super Aci 3 ml/liter, and Nasa 150 ml/plant. The results showed that the age at transplanting and the type of liquid organic fertilizer showed an interaction on the observed parameters of the number of leaves and stem diameter. The age of transplanting 10 days and the type of NPK fertilizer 20 grams/plant showed the highest yield on the parameters of observing the number of leaves and stem diameter.